Numerical simulation of solidification inside a cavity based on the enthalpy formulation - Duan, Qiang. (2008)
Numerical simulations are conducted to study the solidification problem with natural convection inside a rectangular cavity. The cavity is cooled on one vertical wall and is kept adiabatic at other walls. Constant temperature or constant heat flux boundary conditions are applied at the cold wall. The effect of initial liquid superheat and aspect ratio of the cavity is also studied in terms of solid fraction and phase front propagation. Based on the enthalpy formulation, algorithms for both pure material (n-hexadecane) and binary alloy (ammonium chloride water solution) are developed and implemented using a commercial software PHOENICS. The algorithms are iterative in nature and are verified against benchmark solution and experimental data.